“БЕОВУЛЬФ” ВА “АЛПОМИШ” ДОСТОНЛАРИДА ХАЛҚПАРВАРЛИК ҒОЯЛАРИНИНГ БАДИИЙ ИФОДАСИ (Scientific journal of the Fergana State University, 2023)
This article analyses the literary ideas of patriotism, manhood and humanity in poems “Beowulf” and “Alpamish”.